The minimum site investigation requirements needed to define site conditions considering the results of ground investigations and its true reflection of actual site conditions found during construction - Myburgh, Keshia Shermane (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.